2012
DOI: 10.1016/j.jim.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive high throughput ELISA for human eosinophil peroxidase: A specific assay to quantify eosinophil degranulation from patient-derived sources

Abstract: Quantitative high throughput assays of eosinophil-mediated activities in fluid samples from patients in a clinical setting have been limited to ELISA assessments for the presence of the prominent granule ribonucleases, ECP and EDN. However, the demonstration that these ribonucleases are expressed by leukocytes other than eosinophils, as well as cells of non-hematopoietic origin, limits the usefulness of these assays. Two novel monoclonal antibodies recognizing eosinophil peroxidase (EPX) were used to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
2
39
2
Order By: Relevance
“…ECP is an eosinophil granule protein that correlates well with cytokines (eg, interleukin 5 [IL-5] and IL-13) and chemokines (eg, eotaxin-2/CCL24 and eotaxin-3/CCL26) as well as blood and tissue eosinophilia. 9, 24, 25 In prior studies, we found that NP has higher levels of ECP than uncinate tissue (UT) even among patients with CRSwNP. More recently, we found that although ECP levels measured in NP were higher than in UT, UT ECP levels were moderately to strongly correlated with radiographic severity and other type-2 mediators.…”
mentioning
confidence: 85%
“…ECP is an eosinophil granule protein that correlates well with cytokines (eg, interleukin 5 [IL-5] and IL-13) and chemokines (eg, eotaxin-2/CCL24 and eotaxin-3/CCL26) as well as blood and tissue eosinophilia. 9, 24, 25 In prior studies, we found that NP has higher levels of ECP than uncinate tissue (UT) even among patients with CRSwNP. More recently, we found that although ECP levels measured in NP were higher than in UT, UT ECP levels were moderately to strongly correlated with radiographic severity and other type-2 mediators.…”
mentioning
confidence: 85%
“…[4][5][6] A paper-based colorimetric LFT was developed using the wellknown antibody sandwich format ( Figure 1A). 5 As expected, samples from patients with "controlled" inflammation, that is, sputum eosinophils < 3% of total cells (with a total cell count less than 9.7 million cells) 8 showed lower EPX content compared to the "eosinophilic" group with > 3% eosinophils ( Figure 1D, P = .028). The LFTs were imaged using a Flip-Pal (#100C) handheld scanner 15 min after sample addition (details of method development and materials have been provided in the online repository).…”
Section: Rapid Quantification Of Sputum Eosinophil Peroxidase On a Lamentioning
confidence: 99%
“…Although levels of MBP, ECP, EDN and EPO in serum, other body fluids, and cell supernatants can be measured by radioimmunoassay (RIA) (Wassom et al, 1981; Peterson et al, 1991; Robinson et al, 1995) and enzyme-linked immunosorbent assay (ELISA) (Reimert et al, 1991b; Yamamoto et al, 1994; Morioka et al, 2000; Ochkur et al, 2012), both of these methods are time-consuming and measure each granule protein individually. Suspension array technology has the potential to circumvent both of these problems and has been used for the sensitive and simultaneous measurement of multiple proteins in a wide variety of clinical samples, including serum, plasma, cerebrospinal fluid (Moller, 2012), sputum (Bafadhel et al, 2012) and urine (Campbell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%